Harnessing radiotherapy-induced NK-cell activity by combining DNA damage–response inhibition and immune checkpoint blockade. Issue 3 (21st March 2022) - Patin, Emmanuel C; Dillon, Magnus T; Nenclares, Pablo; Grove, Lorna; Soliman, Heba; Leslie, Isla; Northcote, Davina; Bozhanova, Galabina; Crespo-Rodriguez, Eva; Baldock, Holly; Whittock, Harriet; Baker, Gabriella; et al.
Abstract : Background: Despite therapeutic gains from immune checkpoint inhibitors (ICI) in many tumor types, new strategies are needed to extend treatment benefits, especially in patients failing to mount effective antitumor T-cell responses. Radiation and drug therapies can profoundly affect the tumor immune microenvironment. Here, we aimed to identify immunotherapies to increase the antitumor response conferred by combined ataxia telangiectasia and Rad3-related kinase inhibition and radiotherapy. Methods: Using the human papillomavirus (HPV)-negative murine oral squamous cell carcinoma model, MOC2, we assessed the nature of the antitumor response following ataxia telangiectasia and Rad3-related inhibitor (ATRi)/radiotherapy (RT) by performing RNA sequencing and detailed flow cytometry analyses in tumors. The benefit of immunotherapies based on T cell immunoreceptor with Ig and ITIM domains (TIGIT) and Programmed cell death protein 1 (PD-1) immune checkpoint blockade following ATRi/RT treatment was assessed in the MOC2 model and confirmed in another HPV-negative murine oral squamous cell carcinoma model called SCC7. Finally, immune profiling was performed by flow cytometry on blood samples in patients with head and neck squamous cell carcinoma enrolled in the PATRIOT clinical trial of combined ATRi/RT. Results: ATRi enhances radiotherapy-induced inflammation in the tumor microenvironment, with natural killer (NK) cells playing a central role in maximizing treatment efficacy. We demonstrated that antitumor activity of NK cells can be further boosted with ICI targeting TIGIT and PD-1. Analyses of clinical samples from patients receiving ATRi (ceralasertib) confirm the translational potential of our preclinical studies. Conclusion: This work delineates a previously unrecognized role for NK cells in the antitumor immune response to radiotherapy that can be augmented by small-molecule DNA damage–response inhibitors and immune checkpoint blockade.